Pengaruh Kebijakan Proteksionisme Terhadap Hubungan Dagang Antar Negara - Matondang, Khairani Alawiyah; Sinaga, Dewi Larasati; Tinambunan, Fitry Ulinda; Saragi, Sarah Lylia; Sitio, Veranita (Innovative: Journal Of Social Science Research, 2024)
Protectionist policies have been a strategy often adopted by countries seeking to protect their domestic industries from global competition. This strategy includes implementing tariffs, quotas, and various other trade barriers to reduce imports. Although its primary goal is to support domestic economic growth and preserve jobs, protectionism often has unintended consequences on trade relations between countries. This research aims to analyze the influence of protectionist policies on the dynamics of international trade. Through quantitative and qualitative approaches, this study shows how tariffs and trade barriers affect the flow of goods and services between countries. The research results show that protectionism tends to lead to reduced trade volumes, increased consumer prices, and disruption to global supply chains. In addition, protectionist policies can trigger retaliatory actions from affected countries, which can repel diplomatic and economic relations. In the long term, protectionism can hinder innovation and economic efficiency by reducing competition and limiting international cooperation. The study recommends that while protectionism may provide short-term benefits for certain countries, a more open and collaborative approach to international trade would be more beneficial in the long run. Involvement in the multilateral trading system and free trade agreements can encourage inclusive and sustainable economic growth.